A novel model for determining the amplitude-wavelength limits of track irregularities accompanied by a reliability assessment in railway vehicle-track dynamics. (1st March 2017) - Xu, Lei; Zhai, Wanming
Abstract: The loads on a vehicle and the vibrations transmitted to track infrastructures due to the operation of rolling stocks are mainly determined by the irregularities of the track profile. Hence, it is rather important to ascertain the limits of track irregularities, including amplitudes and wavelengths, to guarantee the dynamic performance of running vehicles and guiding tracks. Furthermore, the operation and management levels as well as irregularity status for different railways are highly dissimilar. Therefore, it is a necessary to conduct a reliability assessment for a specific railway line. In the present work, a large amount of measured track irregularities are concentrated as a group form of the track irregularity power spectrum density. A track irregularity inversion model is presented to obtain realistic representations of track profile deformations with information regarding amplitudes, wavelengths and probabilities. Then, the methodologies for determining the limits of track irregularities and achieving a reliability assessment are presented by introducing the probability density evolution method and development of a Wavelet-Wigner-Hough method. Using the vehicle-track interaction model, numerical studies for confirming the limits of track irregularities and evaluating the reliability of the dynamic performance of the vehicle can be conducted to provide valuable suggestions. This paper offers new possibilities for studying the limit amplitudes, characteristic wavelengths of track irregularities as well as corresponding reliabilities when a railway vehicle runs under different track geometric conditions. Highlights: A 3-D linear vehicle-slab track interaction model by combining FEM with wheel-rail coupling mechanism. New methodologies on confirming the limits of track irregularities for guaranteeing the dynamic performance of railway system. Novel model for reliability assessment of railway vehicle-track interactions induced by track profile deformations.